Should Islamic Religious Education and Student Mental Health: Exploring Spiritual Well-Being in Educational Settings in India - Mary Chandana (Muaddib: Jurnal Pendidikan Agama Islam, 2024)
Mental health has become an increasingly important concern in educational settings due to rising levels of stress, anxiety, depression, emotional instability, and psychological challenges among students. In India, academic pressure, social expectations, economic inequality, cultural diversity, and post-pandemic educational disruptions have intensified mental health concerns among learners. Islamic Religious Education (IRE) has the potential to contribute positively to student mental health by promoting spiritual well-being, emotional resilience, moral development, and psychological balance through religious teachings and values. This study explores the role of Islamic Religious Education in supporting student mental health and spiritual well-being in educational settings in India. Using a qualitative literature review approach, the study examines scholarly literature related to mental health, spiritual well-being, Islamic education, and student psychological development. The findings indicate that Islamic Religious Education positively contributes to students’ emotional stability, coping mechanisms, sense of meaning, social connectedness, and psychological resilience through teachings emphasizing faith (iman), patience (sabr), gratitude (shukr), trust in God (tawakkul), and ethical conduct. Furthermore, spiritual practices such as prayer, Qur’anic reflection, and moral guidance may reduce emotional distress and strengthen students’ psychological well-being. However, challenges remain, including stigma surrounding mental health, limited integration between mental health education and religious instruction, insufficient teacher preparedness, and varying cultural perceptions regarding psychological support. The study concludes that Islamic Religious Education can play a meaningful role in promoting student mental health and spiritual well-being in India when supported by inclusive educational approaches, teacher training, and integration between religious values and psychological well-being frameworks.